Unleaded how changing our gasoline changed everything - Nielsen, Carrie (Rutgers University Press, 2021)
"Americans of all political stripes are debating the appropriate use of scientific information in public policy. Unleaded: How Changing Our Gasoline Changed Everything brings a historical perspective to this debate by examining some of the outcomes of applying (or failing to apply) sound science in policymaking. In the 1920s, public health experts failed to convince the government to ban leaded gasoline, and generations of American children paid the price. By the 1970s, children nationwide were lead poisoned at a rate twenty times higher than what Flint, Michigan experienced during its recent water crisis. Eventually, as scientific evidence increasingly demonstrated the damage that lead exposure does to the developing brains of children, the federal government banned leaded gasoline and the amount of lead in the bodies of American preschool children went down by more than 90%. Recent generations, exposed to far less lead than their parents were, and have grown up less likely to drop out of school, have an unwanted pregnancy, or commit a violent crime"--